INSTITUTIONAL ARCHITECTURE AND POWERS OF PUBLIC AUTHORITIES IN FORMING AND IMPLEMENTING SCHOOL HEALTH POLICY IN UKRAINE - Slyvka, Yevheniia (Public Management and Policy, 2026)
The Constitution of Ukraine and current legislation define schoolchildren’s health as a priority of state policy. However, a significant gap remains between normative declarations and practical implementation of health-preserving policy in secondary education institutions. The study analyzes the system of legal regulation of schoolchildren’s health preservation in Ukraine through qualitative content analysis of normative documents adopted during 1992-2025. The research examined 15 normative acts and identified 63 references to the concept of “health” within eight categories of legal regulation, including the right to health protection, children’s health, sanitary norms, and environmental and mental health. The study also revealed five main approaches to defining health in Ukrainian legislation and analyzed the distribution of responsibilities among state authorities at different levels. The findings identified six interrelated problems affecting the effectiveness of health policy implementation in schools. These include the inconsistency between declared goals and implementation mechanisms, institutional discoordination between the Ministry of Health, the Ministry of Education and local authorities, insufficient financial support, fragmentation of legal regulation, weak monitoring mechanisms focused mainly on documentation, and the unclear professional status of school nurses. The results confirm the need to move from fragmented regulation toward systemic integration of health-preserving approaches into educational policy. This requires the development of an interministerial strategy, coordinated governance mechanisms, targeted resource provision, and effective monitoring based on health outcomes. Schoolchildren’s health should therefore be considered not only as a pedagogical or medical issue, but also as an object of state policy and intersectoral governance requiring comprehensive institutional reform.